H.L. Martensen og D.G. Monrad: to biskoppers økonomi - Kærgård, Niels (Kirkehistoriske Samlinger, 2018)
I 1870’erne udgav Hans Lassen Martensen to værker, der gav anledning til en omfattende debat, Den Christelige Ethic, bind II, 2. halvbind: Den sociale Ethik fra 1878 og fortrykket Socialisme og Christendom på 55 sider fra 1874. Ditlev Gothardt Monrad svarede i 1878 med bogen Liberalismens Gjenmæle til Biskop Martensens sociale Ethik. Denne debat mellem to af den danske kirkes fremmeste mænd er nok den grundigste debat, vi har haft på dansk af forholdet mellem markedsøkonomi og kristendom. Og den spredte sig; der kom utallige indlæg i aviser og tidsskrifter samt en lang række debatbøger af forskellige elever og tilhængere af de to biskopper. I denne artikel redegøres dels for Martensen og Monrads synspunkter, og dels for den efterfølgende debat herunder også samtidens økonomers syn på problemstillingerne. Summary A remarkable discussion of the ethics of the capitalistic market economy took place in Denmark in the 1870s. The main contributors were Bishop Hans Lassen Martensen (1808-1884) and Bishop Ditlev Gothardt Monrad (1811-1887), two of the most prominent figures in the ecclesiastical history of Denmark. Martensen published a small pamphlet entitled Socialisme og Christendom (Socialism and Christianity) in 1874, in which he argued against capitalism, individualism and liberalism. He included the text almost unchanged in his major work Den Christelige Ethik (The Christian Ethics) volume II.2 of 1878. Bishop Monrad replied in his book Liberalismens Gjenmæle til Biskop Martensens sociale Ethik (The reply of Liberalism to Bishop Martensen). The two great personalities presented their views profound and clearly, but their elevated position constrained them from engaging in a continuing public debate. Martensen never responded to the objections to his books. Both men were at the end of their careers, so public debate was something they handed over to their students and followers. Nevertheless, an important and interesting debate continued in subsequent years. Almost all major newspapers and a number of journals and magazines carried reviews and comments. Some of the more profound comments were also published as books and pamphlets. The debate is interesting for at least two reasons. First, it is the most thorough debate in Denmark among Christians about what the attitude to social issues should be. Is it a Christian duty to fight for the weak and poor, or should Christianity leave it to the politicians to address social questions? Never before or since have these questions been so intensively debated among so prominent leaders of the Danish church. Secondly, there seems to run a causal chain from Martensen’s contribution to the establishment of the modern welfare state. Not, perhaps, a clear and dominating track, but never the less one of the many threads that were woven together into the fabric that formed the Danish welfare state. The influence brought on this from Hans Lassen Martensen to Fernando Linderberg (1854-1914) and from Linderberg to K.K. Steincke (1880-1963) is well documented, and if one man has to be named as the Father of the Danish welfare state, then K.K. Steincke must be amongst the absolute favourites.